Good Corporate Governance Mediates The Effect of Taxes on Transfer Pricing In Creating a GOLD Indonesia 2045 - Paul Usmany (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Transfer pricing (TP) practices by multinational corporations (MNCs) are a crucial issue in tax administration that has the potential to reduce the domestic tax base, a significant threat to state revenue collection efforts needed to realize Indonesia Emas 2045. This study aims to examine the mediating role of Good Corporate Governance (GCG) in the relationship between taxes (proxied by tax rates) and corporate decisions to conduct transfer pricing . Based on Agency Theory , differences in interests between principals (owners/tax authorities) and agents (management) can encourage aggressive TP practices aimed at minimizing tax burdens. GCG, through principles such as transparency, accountability, and independence, is expected to act as an effective internal and external monitoring mechanism . The proposed research method is a quantitative approach with path analysis on data from MNC companies listed on the Indonesia Stock Exchange (IDX) during a certain period. The expected results are to prove that GCG not only weakens the tax incentives for aggressive TP (moderation role), but also forms a more responsible channel in determining transfer prices that is in line with the Arm's Length Principle . These findings will emphasize that the synergy between strict tax regulations and strong GCG implementation is key to ensuring sustainable tax compliance, creating a healthy investment climate, and supporting state financial accountability which is vital for achieving Indonesia's long-term development vision.